Blurry - Shaw, Dash (New York Review Comics, 2024)
"A man can't decide between two dress shirts for a wedding. A woman questions the style of her new glasses and her engagement. A figure-drawing model considers quitting posing. The figure-drawing model's teacher considers quitting teaching. A man drives into a fog bank and is unsure of how to get home. From Dash Shaw, the author of one of the New York Times Best Comics of 2021, comes a new graphic novel, Blurry. In Blurry, Shaw renders the doubts around everyday decisions as startling cliffhangers, presenting us with the kinds of choices that can make a life expand or contract in equal measure. Depicted in clear lines and washes, Shaw captures the humor and anxiety of life in a one-of-a-kind structure that bends back to a thrilling finale, revealing the web of connections that unites us all. Blurry is more evidence that Shaw is one of our greatest contemporary cartoonists, able to challenge and expand the form of comics while offering captivating stories that resonate with the everyday parts of life"--